How Workload Leads to Burnout: The Mediating Roles of Job Stress and Work-Life Balance - Kurnia, Dwi Irma; Noermijati; Juwita, Himmiyatul Amanah Jiwa (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2026)
This study aims to analyze the effect of workload on burnout, with job stress and work-life balance as mediating variables. The data consisted of 235 employees, whose information was obtained through an online questionnaire that distributed to civil servants at BPS (Badan Pusat Statistik) throughout Bengkulu province. The collected data was then analyzed using the Structural Equation Modeling (SEM) with the SmartPLS software. This study show that workload does not directly lead to burnout but exerts its influence indirectly by significantly increasing job stress and reducing work–life balance. Job stress fully mediates the relationship between workload and burnout, whereas work–life balance neither predicts burnout nor functions as a mediating mechanism. Overall, burnout among civil servants is driven more by psychological strain than by workload intensity alone, reinforcing the explanatory power of the Job Demands–Resources (JD-R) Model framework in the public sector context.